PENGARUH MOTIVASI KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PT. POS INDONESIA (PERSERO) CABANG NGANJUK - Aprilia Dian Evasari; Budi Prasetyo (Universitas Tulungagung, 2023)
Abstract This study discusses the effect of work motivation (X1) and organizational commitment (X2) on employee performance (Y) at PT. Pos Indonesia (Persero), Nganjuk Branch. The sampling technique in the study used non probability sampling techniques or saturated samples. So the number of samples used in this study are all employees at PT. Pos Indonesia (Persero), Nganjuk Branch as many as 43 people. The independent variables of this research are work motivation and organizational commitment to employee performance as the dependent variable. Based on what has been done, it shows that the Work Motivation variable has a significant effect on employee performance partially with a sig. t 0,004 <0,05 and the organizational commitment variable has a significant effect on employee performance partially with a sig. t 0,046 <0,05. For the F test, work motivation and organizational commitment variables have a significant effect on employee performance simultaneously with a significance value 0.000 <0,05.